Pengaruh Penggunaan Media Audio Visual Terhadap Kemampuan Menulis Teks Puisi Siswa Kelas X di SMA Manggala Sakti - Nur Aini; Tsalitsatul Maulidah; Sukiman (Medan Resource Center, 2021)
This research was conducted to determine learning outcomes in writing poetry texts using audio visuals for X grade students of SMA Manggala Sakti in the 2020/2021 academic year. This research is a quasi-experimental research conducted in class X SMA Manggala Sakti. The research subjects were all students of class X with a total of 16. This study was a quasi-experimental population in this study were students of class X even semester of SMA Manggala Sakti. The data of this study were taken from the poetry text writing test. Based on the results of the tests that have been carried out, it was found that there were differences in the results of writing poetry by students using audio-visual media. The results show that Ho is rejected, and Hi is accepted from the t-test hypothesis testing at a significant level of 0.05 with T count (3.91) and T table (0.68), so the results show a significant difference. The first average value was 59.06 to 78.43. This shows a significant increase with a difference of 19.37 increase. Thus, giving treatment in the form of audio-visual media in class X SMA Manggala Sakti got results that were in line with expectations.